An observation of a photovoltaic effect in MoS2 nanoribbons fabricated with a top-down approach. (1st March 2023) - Zhang, Shaochun; Xue, Mengsong; Zeng, Fanyu; Kitaura, Ryo
Abstract: We observed a photovoltaic effect in MoS2 nanoribbons prepared by a top-down approach. Two-terminal MoS2 nanoribbons devices show a non-zero short-circuit photocurrent in response to light excitation; the photocurrent density reached ∼5 × 10 0 A cm −2 at a power of ∼10 4 W cm −2 . Photocurrent mapping has revealed that the photocurrent predominantly emerges when we locate the laser spot on the nanoribbon region, far from electrode contacts, ensuring the photovoltaic effect arises from the MoS2 nanoribbon itself. We also found that light polarization of the photocurrent exhibited direction dependence with a period of 180°. This work has successfully shown that an emerging property can be seen by forming nanoribbons, providing a simple approach to obtaining materials exhibiting photovoltaic effects.